KAJIAN FUNGSI DAN ORGANOLOGI ALAT MUSIK TEGANING PADA MASYARAKAT GAYOKECAMATAN BEBESEN KABUPATEN ACEH TENGAH - Angeline Trianita (Grenek: Jurnal Seni Musik, 2019)
This study aims to discuss the selection of materials in making Teganing musicalinstruments, reviewed from the process of making Teganing, organological studies ofTeganing musical instruments, and reviewing the functions of Teganing musical instrumentsin the Gayo community in Bebesen District, Central Aceh Regency. The theories used in thisresearch are organology theory, musical instrument theory, Teganing theory, and musicfunction theory. This research was conducted on August to October 2018 on the streetPegasing Bebesen District, Central Aceh Regency. The method in this study is descriptivequalitative. The sample in this study amounted to two people, one artist and one Teganingcraftsman. Data collection techniques used were observation, interviews, and documentation.The results of this study explain that Gayo Teganing is made of bamboo (grind) Regen andrequires a long time for the manufacturing process. Teganing is a musical instrument playedby hitting it with a stick (Pegeul) on the string with the right hand and the left hand hittingthe Teganing body instead of repa'i or gegedem as a behavior. The production of GayoTeganing sound produced by the body of the tool itself is present in resonance (vibration)and also the quality of the bamboo used. Functions contained as emotional expressions,entertainment at various levels of socialism, symbolic representation, physical responsetools, reinforcement of social norm conformity, contribute to continuity and cultural stability,supporting social integration.